Spin-label studies of lipid-protein interactions with reconstituted band 3, the human erythrocyte chloride-bicarbonate exchanger. - Taylor, A; Watts, A (1998)
Lipid-protein interactions in reconstituted band 3 preparations were investigated by using spin-labeled lipids in conjunction with electron paramagnetic resonance (EPR) spectroscopy. Purified erythrocyte band 3 was reconstituted into egg phosphatidylcholine liposomes at high protein density with preservation predominantly of the dimeric state. Lipid-protein associations were revealed by the presence of a component in the EPR spectra that, when compared to spectra obtained from protein-free bilayers, indicated that lipid chain motions are restricted by interactions with the protein. From the fraction of the motionally restricted component obtained from the phosphatidylcholine spin-label, a value of 64 +/- 14 annular lipids per band 3 dimer was obtained. This agrees with a value of 62 for the number of lipids that may be accommodated around the electron density map of a band 3 dimer. Selectivity of various spin-labeled lipids for the protein revealed that androstanol had a lower affinity for the band 3 interface, whereas a distinct preference was observed for the negatively charged lipids phosphatidylglycerol and stearic acid over phosphatidylcholine. This preference for negatively charged lipids could not be screened by 1-M salt, indicating that electrostatic lipid-protein interactions are not dominant. Estimates of annular lipid exchange rates from measured acyl chain segmental motions suggested that the rate of exchange between bilayer and boundary lipids was approximately 10(6) s(-1), at least an order of magnitude slower than the rate of lipid lateral diffusion in protein-free bilayers.